2019
DOI: 10.1038/s41598-019-53519-1
|View full text |Cite
|
Sign up to set email alerts
|

Slitrk2 controls excitatory synapse development via PDZ-mediated protein interactions

Abstract: Members of the Slitrk (Slit- and Trk-like protein) family of synaptic cell-adhesion molecules control excitatory and inhibitory synapse development through isoform-dependent extracellular interactions with leukocyte common antigen-related receptor protein tyrosine phosphatases (LAR-RPTPs). However, how Slitrks participate in activation of intracellular signaling pathways in postsynaptic neurons remains largely unknown. Here we report that, among the six members of the Slitrk family, only Slitrk2 directly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…The following commercially available antibodies were used: mouse monoclonal anti-HA (clone HA-7; Covance), mouse monoclonal anti-FLAG M2 (Sigma-Aldrich), rabbit polyclonal anti-FLAG (Sigma-Aldrich), goat polyclonal anti-EGFP (Rockland Immunochemicals), mouse monoclonal anti-NL-1 (clone N97A/31; Neu-roMab), rabbit polyclonal anti-NL-2 (Synaptic Systems, Göttingen, Germany), rabbit monoclonal anti-TrkC (clone C44H5; Cell Signaling Technology), guinea pig polyclonal anti-VGLUT1 (Millipore), mouse monoclonal anti-GAD67 (clone 1G10.2; Millipore), mouse monoclonal anti-PSD-95 (clone K28/43; Thermo Fisher Scientific), mouse monoclonal anti-b-actin (clone AC-74; Sigma-Aldrich), mouse monoclonal anti-parvalbumin (clone PARV-19; Millipore), mouse monoclonal anti-gephyrin (clone 3B11; Synaptic Systems), rabbit polyclonal anti-GABA A receptor g2 (Synaptic Systems); mouse monoclonal anti-GluN1 (clone 54.1; Millipore), rabbit polyclonal anti-GluN2A (Millipore), rabbit polyclonal anti-GluN2B (Millipore), goat anti-human IgGperoxidase (Sigma-Aldrich), and mouse monoclonal anti-NeuN (clone A60; Millipore). The following antibodies have been previously described: anti-PSD-95 (JK016) (20), anti-synapsin (JK014) (37), anti-GAD65 (JK158) (38), anti-Clstn3 (JK001) (15), anti-GluA1 (1193) (39), and anti-GluA2 (1195) (39).…”
Section: Antibodiesmentioning
confidence: 99%
“…The following commercially available antibodies were used: mouse monoclonal anti-HA (clone HA-7; Covance), mouse monoclonal anti-FLAG M2 (Sigma-Aldrich), rabbit polyclonal anti-FLAG (Sigma-Aldrich), goat polyclonal anti-EGFP (Rockland Immunochemicals), mouse monoclonal anti-NL-1 (clone N97A/31; Neu-roMab), rabbit polyclonal anti-NL-2 (Synaptic Systems, Göttingen, Germany), rabbit monoclonal anti-TrkC (clone C44H5; Cell Signaling Technology), guinea pig polyclonal anti-VGLUT1 (Millipore), mouse monoclonal anti-GAD67 (clone 1G10.2; Millipore), mouse monoclonal anti-PSD-95 (clone K28/43; Thermo Fisher Scientific), mouse monoclonal anti-b-actin (clone AC-74; Sigma-Aldrich), mouse monoclonal anti-parvalbumin (clone PARV-19; Millipore), mouse monoclonal anti-gephyrin (clone 3B11; Synaptic Systems), rabbit polyclonal anti-GABA A receptor g2 (Synaptic Systems); mouse monoclonal anti-GluN1 (clone 54.1; Millipore), rabbit polyclonal anti-GluN2A (Millipore), rabbit polyclonal anti-GluN2B (Millipore), goat anti-human IgGperoxidase (Sigma-Aldrich), and mouse monoclonal anti-NeuN (clone A60; Millipore). The following antibodies have been previously described: anti-PSD-95 (JK016) (20), anti-synapsin (JK014) (37), anti-GAD65 (JK158) (38), anti-Clstn3 (JK001) (15), anti-GluA1 (1193) (39), and anti-GluA2 (1195) (39).…”
Section: Antibodiesmentioning
confidence: 99%
“…The study characterizing Slitrk3 KO mice has further supported selective involvement of Slitrk3 in inhibitory synapse development (Takahashi et al, 2012 ) by detecting a decrease in inhibitory synapse number and function as well as seizure behaviors. On the other hand, RNAi-based knockdown studies as well as neuronal overexpression ones have indicated selective involvement of Slitrk1/2 in excitatory synapse number and function (Yim et al, 2013 ; Schroeder et al, 2018 ; Han et al, 2019 ). Also, Slitrk1 KO mice exhibit elevated anxiety behaviors (Katayama et al, 2010 ), and Slitrk5 KO mice display obsessive-compulsive–like behaviors with decreases in glutamate receptors and excitatory synaptic transmission in cortico-striatum synapses (Shmelkov et al, 2010 ).…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…Having seen the functional alteration of mossy fiber-CA3 synapses, we investigated the synapse morphology. Because Slitrk2 is known to bind PSD-95 ( Han et al., 2019 ; Loomis et al., 2020 ), immunostaining analysis was performed to examine the PSD-95 distribution in the Slitrk2 KO brain ( Figures 5 A and 5B) As a presynaptic marker, VGlut1 was simultaneously detected. In the analysis of PSD-95 + , VGlut1 + , or PSD-95 + VGlut1 + -immunopositive punctate signals, we observed an increase of the PSD-95 + particle sizes in TRN (+2.6%, p = 0.044, n = 7 mice per genotype, p = 4.4 × 10 −5 n = 56 images from seven mice per genotype) and in pontine nuclei (+2.5%, p = 0.067, n = 7 mice per genotype, p = 9.3 × 10 −5 , n = 56 images from seven mice per genotype)( Figure 5 and Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Slitrk2 is highly expressed in immature neural progenitor cells, as well as in mature cells of the CNS, and overexpression of Slitrk2 inhibits nerve growth factor-induced neurite outgrowth in PC12 cells ( Aruga and Mikoshiba, 2003 ). Slitrk2 increases synapse numbers (synaptogenic activity) through its interaction with protein tyrosine phosphate receptors ( Linhoff et al., 2009 ; Takahashi and Craig, 2013 ) in addition to controlling excitatory synapse development through its interaction with membrane associated guanylate kinases such as PSD-95 ( Han et al., 2019 ; Loomis et al., 2020 ). Slitrk2 levels have been shown to be reduced in the neural cells of myotonic dystrophy patients and brain ex vivo tissue, and rescued expression of Slitrk2 recovered the neurite outgrowth deficits in patient-derived cells ( Marteyn et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%